PENGARUH MODEL PEMBELAJARAN PROBING PROMTING BERBANTUAN MEDIA GAMBAR TERHADAP HASIL BELAJAR SISWA - Julia Marsena; Masyhuri Masyhuri; Mila Noviana (Jurnal Pendidikan Sosial Keberagaman, 2026)
Low student learning outcomes are attributed to ineffective classrom learning processes and limited student engagement in learning activities. This study aimed to determine the effect of the probing promting learning model assisted by picture media on students’ learning outcomes in sociology. The research employed a quantitative approach with a quasi-experimental method using a pretest-posttest control group design. The population consisted of 180 eleventh-grade social science students at SMAN 3 Mataram. The sample was selected through a simple random sampling technique after class matching had been conducted, resulting in class XI IPS-6 as the experimental group and class XI IPS-3 as the control group. The research instrument was an essay test that had been previously tested for validity and reliability. Data analysis included descriptive statistics, normality testing, homogeneity testing, and hypothesis testing using the Independent Samples t-test with the assistance of SPSS 26.0 for Windows. The results revealed that the mean learning outcome score of students in the experimental class was 88.17, which was higher than that of the control class at 80.00. The hypothesis testing showed a significance value (Sig. 2-tailed) of 0.000 < 0.05, indicating a significant difference in learning outcomes between the two groups. Therefore, it can be concluded that the implementation of the probing promting learning model assisted by picture media has a positive effect on students’ sociology learning outcomes at SMAN 3 Mataram. Keywords: Probing Promting, Picture Media, Learning Outcomes